2002
DOI: 10.1038/sj.mp.4001059
|View full text |Cite
|
Sign up to set email alerts
|

5HT1Dβ Receptor gene implicated in the pathogenesis of Obsessive-Compulsive Disorder: further evidence from a family-based association study

Abstract: Obsessive-Compulsive Disorder (OCD) is a psychiatric condition with strong evidence for a genetic component and for the involvement of genes of the serotonin system. In a recent family-based association study we reported an association between the G allele of the G861C polymorphism of the 5HT1D␤ receptor gene and OCD. The aim of the present study was to further investigate for the presence of linkage disequilibrium between each of two polymorphisms of the 5HT1D␤ receptor gene and OCD in a larger sample of OCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 28 publications
(33 reference statements)
2
33
0
1
Order By: Relevance
“…Indeed, the absolute role of the HTR1B gene in behavior has been difficult to ascertain, and research on HTR1B has yielded conflicting results in terms of its pharmacology and genetics. Genetic studies have shown an association between variation in the HTR1B gene and a number of phenotypes, including attention deficit hyperactivity disorder, [28][29][30] obsessive compulsive disorder, 31 antisocial alcoholism, 32 substance dependence and major depression. 33 However, many of the association findings have been inconsistent, [34][35][36] and this may be due to an incomplete awareness of the extent of functional variation within the HTR1B gene.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the absolute role of the HTR1B gene in behavior has been difficult to ascertain, and research on HTR1B has yielded conflicting results in terms of its pharmacology and genetics. Genetic studies have shown an association between variation in the HTR1B gene and a number of phenotypes, including attention deficit hyperactivity disorder, [28][29][30] obsessive compulsive disorder, 31 antisocial alcoholism, 32 substance dependence and major depression. 33 However, many of the association findings have been inconsistent, [34][35][36] and this may be due to an incomplete awareness of the extent of functional variation within the HTR1B gene.…”
Section: Discussionmentioning
confidence: 99%
“…The most informative models have used knockout or transgenic mouse models of Sapap3, 5-HT 2C , D1CT and DAT described below, in addition to Slitrk5 [171], and Hoxb8 [172]. In addition, pharmacological assessments in mouse models suggest a possible role for 5-HT 1B receptors in OCD [173,174], with some evidence for a role for 5-HT 1B (5-HT 1Db ) in OCD from human studies as well [175,176]. Further, trichotillomania (TTM) is currently considered an OCD-spectrum disorder characterized by self-induced and recurrent loss of hair [177], and spontaneous barbering has been evaluated in mice of different background strains, and is suggested to be an animal model of TTM [167].…”
Section: (B) Chromosome 22q Deletion Syndromementioning
confidence: 99%
“…World et al found a preferential transmission of the G861 allele for OCD 24 and confirmed these findings in a longitudinal study 25 . Camarena et al also found a preferential transmission of the variant G861 C861 compared to the group with the highest scores of the YBOCS (Yale-Brown Obsessive Compulsive Scale), although no association was found with OCD 26 .…”
Section: Serotonin Receptor Type 1b (Htr1b 5ht1b)mentioning
confidence: 64%